Is Kazan an oriental city? (Based on the guidebook of 1873) - E.M. Dusaeva; N.I. Khanbekova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The guidebook is one of the most genre-defined forms of historical and educational work. Using the example of the text of the “Index of Kazan Historical Sites” by Professor S.M. Shpilevskii, the potential and importance of the guidebook for the formation of historical ideas in society was studied. Since the genre of the guidebook was new during S.M. Shpilevskii’s times, the presence or absence of the signs of a genre standard in this composition were determined. The theoretical basis of the research is the methods of structural analysis, semiotics and memory studies. Based on the results of the analysis of the text of the “Index”, the following methods were distinguished as the characteristic methods of creating the image of Kazan: selection of objects, marking them from more to less significant ones, the historical ideology of the discourse of the events and places described, the use of a certain presentation style and ideological antitheses “ours” – “foreign”. The obtained results show that it is impossible to describe Kazan in the framework of the European tradition; it appears as “its” Orient, an Orient that does not frighten. Kazan is the tamed Orient, the Orient in Western Costume, and the Tatars living in the city, despite being foreigners, are not alien.